Comparison of 123I-MIBG scintigraphy and phosphorylated α-synuclein skin deposits in synucleinopathies. (December 2020) - Giannoccaro, Maria Pia; Donadio, Vincenzo; Giannini, Giulia; Devigili, Grazia; Rizzo, Giovanni; Incensi, Alex; Cason, Ernesto; Calandra-Buonaura, Giovanna; Eleopra, Roberto; Cortelli, Pietro; Liguori, Rocco
Abstract: Introduction: Cardiac [123I]metaiodobenzylguanidine scintigraphy (123I-MIBG) is considered a useful test in differentiating multiple system atrophy (MSA) and Lewy body disorders (LBD), including idiopathic Parkinson's disease (IPD), dementia with Lewy bodies (DLB) and pure autonomic failure (PAF). The detection of skin nerve phosphorylated α-synuclein (p-α-syn) deposits could be an alternative marker in vivo. We sought to compare 123I-MIBG scintigraphy and skin biopsy findings in α-synucleinopathies. Methods: We studied 54 patients (7 DLB, 21 IPD, 13 PAF, 13 MSA) who underwent 123I-MIBG scintigraphy and skin biopsy to evaluate cardiac innervation and skin p-α-syn deposition, respectively. Results: Cardiac denervation was observed in 90.5% IPD, 100% DLB and PAF and in none of the MSA patients (P < 0.0001) whereas p-α-syn deposits were detected in all DLB and PAF, in 95.2% of IPD and 69.2% of MSA patients (P = 0.02). However, the analysis of skin structures disclosed a different distribution of the deposits in somatic subepidermal plexus and autonomic fibers among groups, showing that p-α-syn deposits rarely affected the autonomic fibers in MSA as opposed to LBD. Studying the p-α-syn deposition in autonomic nerves, concordance among I123-MIBG scintigraphy and skin biopsy results was observed in 100% of DLB and PAF, 95.2% IPD and 92.3% MSA patients. I123-MIBG scintigraphy and autonomic p-α-syn deposits analysis both showed a sensitivity of 97.5% and a specificity of 100% and 92.3%, respectively, in distinguishing LBD and MSA. Conclusion: Skin biopsy and 123-MIBG scintigraphy can be considered alternative tests for the differential diagnosis of IPD, PAF and DLB versus MSA. Highlights: Concordant results between 123I-MIBG scintigraphy and skin biopsy were observed in all DLB and PAF, in 95% IPD and 92% MSA. 123I-MIBG scintigraphy and p-α-syn in skin autonomic fibers show similar accuracy in differentiating LBD and MSA. There is a correlation between cardiac denervation and p-α-syn deposition in the autonomic nerves.